A review of the effect of the light environment of the VDT workspace on the “learning to learn” effect of video game training - Cheng, Xiang; Yan, Yonghong; Hu, Tao; Lv, Yinghui; Zeng, Yue (Frontiers in Neuroscience, 2023)
In recent years, the role of video games in enhancing brain plasticity and learning ability has been verified, and this learning transfer is known as the “learning to learn” effect of video game training. At the same time, against the background of healthy lighting, the influence of non-visual effects of light environment on the human rhythmic system has been gradually confirmed. As a special operation form of Visual Display Terminal (VDT) operation, video game training has a high dependence on VDT equipment and the VDT screen, and the background usually has a huge difference in brightness. Compared with the light environment of ordinary operation space, the light environment of VDT operation space is more complex. This complex light environment's non-visual effects cause human emotions, alertness, fatigue, cognitive ability, and other changes, which may affect the efficiency of the “learning to learn” effect of video game training. This article focuses on the impact of the light environment in the VDT workspace on the “learning to learn” effect of video game training. It first traces the factors that trigger the “learning to learn” effect of video game training, that is, the improvement of people's attention, perception, and cognitive ability. Then, the influencing mechanism and the evaluation method of the VDT workspace space light environment on the human rhythm system are discussed based on the basic theory of photobiological effect. In addition, the VDT display lighting light time pattern, photophysical properties, regulation, and protection mechanism on the human rhythm system are studied to demonstrate the VDT workspace light environment's special characteristics. Finally, combined with the progress of artificial lighting technology and the research results of health lighting, given the “learning to learn” effect of video game training, some thoughts on the design of the light environment of the workplace and future research directions are presented.